Characterization and susceptibility of non-albicans Candida isolated from various clinical specimens in Lebanese hospitals - Husni, Rola; Bou Zerdan, Maroun; Samaha, Nadia; Helou, Mariana; Mahfouz, Youssef; Saniour, Rim; Hourani, Sawsan; Kolanjian, Harout; Afif, Claude; Azar, Eid; El Jisr, Tamima; Mokhbat, Jacques; et al. (Frontiers in Public Health, 2023)
Background Invasive fungal infections have presented a challenge in treatment. In the past, it was known that the frontrunner in such infections is Candida albicans with little emphasis placed on non-albicans Candida species (NAC). Studies worldwide have shown a rise in fungal infections attributed to non-albicans Candida species. The aim of this study is to describe the epidemiology of NAC infections along with an overview of resistance in Lebanese hospitals. Methods This is a two-year observational multi-central descriptive study. Between September 2016 and May of 2018, a total of 1000 isolates were collected from 10 different hospitals distributed all over the country. For the culture, Sabouraud Dextrose Agar was used. Antifungal Susceptibility was evaluated by determining the Minimum Inhibitory Concentration (MIC) in broth (microdilution) of the different antifungal treatments. Results Out of the 1000 collected isolates, Candida glabrata, being the most isolated species (40.8%), followed by Candida tropicalis: 231(23.1%), Candida parapsilosis: 103(10.3%), and other NAC species at lower percentage. Most of these isolates (88.67%) were susceptible to posaconazole, 98.22% were susceptible to micafungin, and 10% were susceptible to caspofungin. Conclusion The change of etiology of fungal infections involving a significant increase in NAC cases is alarming due to the different antifungal susceptibility patterns and the lack of local guidelines to guide the treatment. In this context, proper identification of such organisms is of utmost importance. The data presented here can help in establishing guidelines for the treatment of candida infections to decrease morbidity and mortality. Future surveillance data are needed.